Credible online news? yes or no - Ahmad Ghazali, Akmar Hayati; Nurdin, Rahmawati; Sharil Nizam, (David Publishing, 2016)
Dissemination of information medium are no longer limited to newspapers, television and radio but is extending to the online news. The number of online news readers is rapidly increasing along with the popularity of the Internet. However, only sources that emphasizes the element of credibility will be accepted by the readers. This study was conducted to determine the credibility of online news; to identify the relationship between online news credibility and youth acceptance. Using a quantitative approach, a total of 400 youth selected to participate in the study out of the 68,000 population in Selangor. The data was analyzed using Statistical Package for Social Science (SPSS) version 21.0. This study shows that a group of young women were the common group who seek and read online information. Based on the findings too, online news in Malaysia are less credible. Although the online news is less credible, the results shows that youth read online news because the contents are current and up to date. Further, result of the Pearson’s correlation test shows that the more credible elements available in online news, the more that medium is accepted by youth